Three cases of OXA-48-like carbapenemase producing Enterobacteriaceae (not) detected using Xpert® Carba-R. Issue 4 (4th July 2017) - Boelens, Jerina; Yusuf, Erlangga; Decruyenaere, Johan; Coorevits, Liselotte; Piérard, Denis; Claeys, Geert
Abstract : The increasing prevalence of carbapenemase-producing Enterobacteriaceae necessitates laboratories to invest in the detection of these bacteria, both with phenotypic and to a lesser extent molecular methods. OXA-48-like strains are rapidly emerging, especially in Europe. Since the expression level of OXA-48 is low and some strains present with several alleles, some types might be missed by some molecular assays. Three cases of OXA-48-like strains are described here, where the detection was not straightforward.